Partager la fonction répressive : la collaboration entre la police et une compagnie de sécurité privée dans un quartier aisé du Cap - Rachel Roumet (EchoGéo)
Based on a qualitative study launched in a wealthy suburb to the South of Cape Town, this article analyses the transformations in the role of the police caused by appealing to a private security company for maintaining public order. The private security company is in charge of the patrols, which has allowed policemen to reallocate their activities towards the development of community services and crime prevention. The local police and a private company collaborate one with another to form, together with the active participation of inhabitants, an outstanding example of the transformation of security governance in South Africa.